The Effects of Continuous Labor Support by Midwife: A Randomized Controlled Trial - DEMİRGÖZ BAL, MELTEM (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: The aim of this study was to evaluate the effects of continuous labor support by midwife. Methods: This study was a randomized controlled experimental design. Seventy primipara women were randomized into two groups, the continuous labor support by midwife group (n=35) and control group (n=35). In the experiment group was given the continuous midwife support and in the control group were undergone to routine hospital care in the clinic. Visual Analog Scale was used to assess women's anxiety level and coping with labor pain. All interventions and childbirth time were recorded by the researcher. Results: Anxiety level decreased and the level of coping with labor pain increased in the experimental group (p<0.05). The total childbirth time in the intervention group was shorter by 2 hours and 21 minutes. Labor induction, episiotomy, amniotomy and perineal trauma were higher in the control group (p<0.05). Conclusion: Continuous labor support should be provided at each childbirth to enhance childbirth outcomes.
Keywords: Continuous labor support; randomized controlled study; midwife; childbirth; Turkey; URINARY-INCONTINENCE; OUTCOMES; NURSES; INJURY; TERM